RAS Mutations Predict Recurrence-Free Survival and Recurrence Patterns in Colon Cancer: A Unicenter Study in Morocco - Fatima El Agy PhD; Sanae El Bardai PhD; Sara Boukansa PhD; Laila Bouguenouch MD; Zineb Benbrahim MD; Khalid Mazaz MD; El Bachir Benjelloun MD; Abdelmalek Ousadden MD; Karim Ouldim MD; Sidi Adil Ibrahimi MD; Laila Chbani MD (Cancer Control, 2024)
Purpose To date, only a few studies have investigated the role of molecular alterations in cancer recurrence. This exploratory study aimed to evaluate the impact of molecular alterations on the time and site of recurrence in patients with stage I–IV CRC and to identify the risk factors predicting recurrence-free survival in colon cancer. Methods A total of 270 patients were retrospectively included. We assessed the full RAS status using Sanger and pyrosequencing. MSI status was determined by immunohistochemical analysis. Molecular alterations were correlated with recurrence timing (early or late), recurrence patterns, and recurrence-free survival. Statistical analysis was performed using the Kaplan–Meier method and the log-rank test. Results Of the 270 patients, 85 (31%) experienced recurrence, among whom 53% had mutant full RAS status, 48% had KRAS mutations, and 31.4% had KRAS p. G12V mutation subtype. Compared with those with late recurrence, patients with early recurrence were significantly older ( P = 0.02 ) and more likely to have poorly differentiated tumors, a higher rate of positive lymph nodes, KRAS mutations, and especially KRAS p. G12V mutation variant. RAS mutation status, KRAS mutations, and rare mutations are more common in patients with lung cancer recurrence. Multivariate logistic regression analysis revealed that differentiation, perineural invasion, full RAS mutation status, and KRAS codon 13 mutations were independent factors for recurrence-free survival in colon cancer. Conclusion In this cohort, the timing and patterns of recurrence appeared to be associated with the patient’s molecular profile. KRAS codon 12 mutations were the worst predictors of recurrence-free survival at all stages in our population.